ANALISIS PROSES MANAJEMEN RISIKO PERBANKAN DALAM MENGENDALIKAN RISIKO KREDIT (Studi Kasus pada PT Bank Rakyat Indonesia (Persero) Tbk Kantor Cabang Parepare) - Fatima, Fatima (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the role of risk management in controlling credit risk. To apply these objectives, descriptive quantitative methods are used. Secondary data were processed using the Non-Performing Loan formula, while the in-depth data was extracted through interview techniques. Secondary data was collected in a time series for three years of observation, namely data for 2017, 2018, and 2019. The results showed that the role of banking risk management in controlling credit risk has not been maximally carried out even though in its implementation it is by the 5C measurement. This result is supported and proven by the number of bad loans which has increased for three consecutive years, namely in 2017, 2018, and 2019 with a total of 28.786.767.971, 32.650.807.563, 40.379.887.745